THE DISBURSEMENT POLEMIC OF OLD AGE SECURITY BENEFITS: UTILITARIANISM PERSPECTIVE - Ayu Divia Suryasha Manuaba, Ida (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
This paper aims to analyze the regulations in term of disbursing the benefits of the old age security program and the perspextive of utilitarianism toward the polemic of disbursing old age security benefits. The method used in writing this scientific paper is a normative legal research method paying attention to the bluriing of norm from indications of inconsistencies in regulations on the disbursement of old age security benefits as well as a conceptual approach from the perspective of utilitarianism and related legal theories. The result of the writing are that the regulation on the disbursement of old age security benefits which includes rules for stopping work for reason of registration and termination of employment is nit in accordance with the essence of old age security protection so there is a blurring of norm. The old age security program as one of the social guarantees that provides protection for workers as their basic rights is part of the embodiment of the concept of a welfare state which originates from the notion of utility, creating the highest possible happiness for the community is the goal of legal benefit, but if the benefit paying more attention to individual interest will harm social justice and inconsistently formed laws will harm legal certainty, so that there is a blurring of norms which certainly does not reflect good law.